Pengaruh Variasi Kecepatan Udara Terhadap Nilai Fuel Convertion Rate Insenerator Fluidized Bed Dengan Bed Material Pasir Besi - Binawangsa, Anandha; Winaya, I Nyoman Suprapta; Suryawan, I Gede.Putu.Agus (Teknik Desain Mekanika, 2022)
Abstract Fluidized bed incinerator technology.can.be.used.to.reduce medical waste which hasXincreasedXdueLtoItheICOVID-19 pandemic. OneIofItheIimportantIindicatorsIthat can affectLthe works of theLincinerator is air flowIvelocity. In this study, variations in the reactor inlet velocity were carried out at a speed of 3.m/s;i3.5im/s;i4im/s;i4.5im/s;iandi5 m/s. The result of this research is the.air.velocity of 3.5.m/s has.the.highest efficiency value compared to other velocity variations, which is 4,880 kg/h. This happened because the bed material in this velocity works more optimally in capturing exhaust gas emissions due to more evenly distributed fluidization in the reactor which will affect the amount of gas emissions released into the environment less than other variations. Keywords: medical waste, fluidized bed, air flow velocity, fuel convertion ratio